2015
DOI: 10.1016/j.jmb.2015.06.011
|View full text |Cite
|
Sign up to set email alerts
|

ClickSeq: Fragmentation-Free Next-Generation Sequencing via Click Ligation of Adaptors to Stochastically Terminated 3′-Azido cDNAs

Abstract: We present a simple method called ‘ClickSeq’ for Next-Generation Sequencing (NGS) library synthesis that uses click-chemistry rather than enzymatic reactions for the ligation of Illumina sequencing adaptors. In ClickSeq, randomly-primed reverse transcription reactions are supplemented with azido-2’,3’-dideoxynucleotides that randomly terminate DNA synthesis and release 3’-azido blocked cDNA fragments in a process akin to dideoxy-sanger sequencing. Purified fragments are ‘click-ligated’ via copper-catalyzed alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
98
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(101 citation statements)
references
References 43 publications
(50 reference statements)
3
98
0
Order By: Relevance
“…The encapsidated genomic RNA was then extracted and prepared for RNAseq using ClickSeq (a cDNA library generation method we recently developed that considerably reduces artifactual recombination[21]). Final cDNA sequencing libraries were prepared for paired-end sequencing with an average fragment length of 150–200bps and sequenced on an Illumina NextSeq giving 150bp for each read.…”
Section: Resultsmentioning
confidence: 99%
“…The encapsidated genomic RNA was then extracted and prepared for RNAseq using ClickSeq (a cDNA library generation method we recently developed that considerably reduces artifactual recombination[21]). Final cDNA sequencing libraries were prepared for paired-end sequencing with an average fragment length of 150–200bps and sequenced on an Illumina NextSeq giving 150bp for each read.…”
Section: Resultsmentioning
confidence: 99%
“…This design allows for cDNA chain termination to occur only in the residues just upstream of poly(A) tail, essentially 'homing-in' on the junction of the 3´UTR and the poly(A) tail. We have found that a ratio of 1:5 AzVTPs:dNTPs reliably yields cDNA fragments ranging from 50-400 nts in length (42).…”
Section: Poly(a)-clickseq Library Generationmentioning
confidence: 98%
“…We recently reported a technique called 'ClickSeq' that uses azido-nucleotide terminators in randomlyprimed RT reactions to produce cDNA fragments from non-fragmented template RNA (42). Azidonucleotides are stochastically incorporated during cDNA synthesis inducing chain-termination yielding a distribution of cDNA fragment lengths, which is determined by the ratio of AzNTPs to dNTPs.…”
Section: Poly(a)-clickseq Library Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, adapter sequences can be ligated to the ends of RNA before reverse transcription, included in the reverse transcription primer or ligated to the cDNA 3′ end. Alternatively, the terminal transferase activity of M-MLV reverse transcriptase can be used in combination with its ability to switch template to add a 3′ cDNA adapter sequence during reverse transcription [6], or reverse transcription can be terminated stochastically with 3′ azido labeled dideoxynucleotides followed by click chemistry-mediated adapter addition [7]. …”
mentioning
confidence: 99%